Training for the Creation of Interactive Learning Videos Lecturers and Students of Islamic Education UIN Mahmud Yunus Batusangkar - Azis, David; Pranata, Rudi; Mastanora, Refika; Maimori, Romi; Adri, Muhammad; riswanto, Riswanto (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2023)
The issues faced by Lecturers and Students of Islamic Education (PAI) at UIN Mahmud Yunus Batusangkar include the suboptimal understanding in preparing teaching materials during field learning practices in schools. Considering the importance of interactive learning media to assist the learning process in schools, there is a need for training in creating interactive video-based learning media through training activities. This training is conducted with the aim of enhancing the knowledge and skills competence of Lecturers and Students of PAI at UIN Mahmud Yunus Batusangkar as prospective teachers who require skills in creating interactive digital-based learning media. This community service activity is carried out using the Participatory Action Research (PAR) method through training activities involving Lecturers and Students. The implementation consists of three stages: (1) pre-activity, (2) activity implementation, and (3) evaluation of the implementation. The results of this activity indicate an improvement in the competence of lecturers and students of Islamic education at UIN Mahmud Yunus Batusangkar in utilizing technology to support the learning process, particularly in creating creative, innovative, and interactive learning videos.